An Unusual Case of Penetrating Ocular Trauma with a Pressure Cooker Whistle - Thapa, Dinesh Kumar; Vyas, Shyam; Saiju, Rohit; Rajbhandari, Pravash; Pant, Basant (Eastern Green Neurosurgery, 2019)
Worldwide blindness in 1.6 million people is due to ocular trauma. Trauma is the most common cause of unilateral loss of vision in developing countries and about 5 % of all bilateral blindness is directly due to trauma. In Nepal, ocular trauma is considered a major cause of unilateral blindness and caused 7.9 % of all blindness in Nepal. It is the second leading cause of blindness after cataract. Pressure cooker is a cooking utensil that works with high pressure and heat, consuming less time and fuel but as seemingly easy, the trouble handling with it could be horrible. It may cause serious injury to someone nearby. Here by, we would like to report a case that could rarely happen in kitchen as a worst accident.